The Opportunities and Challenges of Influencers Collaboration in Modern Public Relations Communication - Marchenko, Valerii; Putranto, Algooth (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2025)
The rapid growth of digital media has transformed modern public relations (PR) practices, emphasizing two-way communication, reputation management, and stakeholder engagement. Influencers have emerged as strategic communicators capable of shaping public perceptions and strengthening organizational communication. Previous studies have predominantly focused on marketing aspects, such as brand attitudes or purchase intentions, leaving limited research on the integration of influencers into long-term PR strategies, strategic influencer selection, and reputation risk management. This study aims to explore the role of influencers in modern PR communication strategies in Jakarta, Indonesia, as well as the opportunities and challenges they present. A qualitative approach was employed through semi-structured in-depth interviews with 15 participants, including PR practitioners and influencer marketing specialists. Data were analyzed using thematic analysis through coding, categorization, and theme development. Findings indicate that influencers act as strategic bridges between organizations and segmented audiences, enhancing message personalization, credibility, engagement, and brand positioning. Micro-influencers, in particular, facilitate higher audience interaction due to interpersonal closeness and community trust. The study concludes that careful influencer selection, ethical guidelines, and ongoing monitoring are key to successful influencer-based PR strategies.